WHAT IS THE ROLE OF MEDIA IN SHAPING CULTURAL IDENTITIES AND VALUES? - Sattorova Mavluda; Fozilbek Orzibekov (TADQIQOTLAR, 2025)
Abstract The media plays a crucial role in shaping cultural identities and values by influencing perceptions, behaviors, and social norms. Through various forms, including television, film, social media, and news outlets, media serves as a powerful tool for disseminating cultural narratives, reinforcing traditions, and introducing new perspectives. It contributes to identity formation by portraying cultural symbols, historical events, and societal expectations, which help individuals develop a sense of belonging. Additionally, globalization has expanded media’s influence, leading to the blending of cultures while also raising concerns about cultural homogenization. While media fosters cross-cultural understanding and appreciation, it can also reinforce stereotypes and biases. Therefore, its role in shaping cultural identities requires critical engagement to promote inclusivity and authenticity. This paper explores how media influences cultural identities and values, examining both its positive and negative impacts on society.